With a Grain of Salt: Concept of Performance and Metalepsis in James Salter's 'Light Years' - Rubtsov, Aleksandr (Satura, 2024)
It is a truth universally acknowledged that having completed a seemingly conventional novel, writers often resort to trickery to keep the readers engaged in the narrative. Whilst some authors may eavesdrop on multiple focalizers, others wallow in a shallow stream of consciousness. The subtlest, however, do neither, and yet exceed all the rest. James Salter, (1925–2015) an American novelist ofmoderate renown, belongs to the latter category.